Ayurvedic Healing D2.5 A Comprehensive Guide - David Frawley_K4.3 (Motilal Banarsidass Publ. Delhi, 2012)
Ayurvedic Healing presents the Ayurvedic treatment of common diseases, covering over eighty different ailments from the common cold to cancer. It provides a full range of treatment methods including diet, herbs, oils, gems, mantra and meditation. The book also shows the appropriate life-style practices and daily health considerations for your unique mind-body type both as an aid to disease treatment and for disease prevention. This extraordinary book is a complete manual of Ayurvedic health care that offers the wisdom of this ancient system of mind-body medicine to the modern reader relative to our special health concerns today. The present edition is a revised and expanded version of the original 1989 edition, covering additional diseases and adding new treatments.
Text language (ISO-639-1 code): en